The Role of Natural Ability and Characteristics of Aviation Security Employees in Implementing Standard Operating Procedures at Lombok International Airport - Yusuf Andi Dwi Satriya; Andi Syaputra (CV. Rayyan Dwi Bharata, 2023)
Security in general is always considered as a guarantee of safety. When there is a problem in a place, it is none other than the security or security forces in that place, like at an airport, security issues are handled by Aviation Security officers. The importance of the natural abilities and characteristics of Aviation Security employees greatly influences the smooth implementation of standard operating procedures which one day will be needed when unexpected problems occur and not only for problems but the natural abilities and characteristics of Aviation Security employees play an important role for the comfort of the services provided for passengers or users of the airport. The purpose of this research is to find out the role of the natural abilities of individual Aviation Security employees in implementing Standard Operating Procedures and the role of the Characteristics of Aviation Security employees in implementing SOPs. This study uses a qualitative method of sampling purposively and snowball, triangulation research technique. The results of Intellectual avation security research in implementing standard operating procedures as research has carried out show that the potential possessed by Aviation Security employees is very influential in providing services to users of aviation services, members or Aviation Security personnel who have intellectual abilities such as having smart minds can carry out security and safety at the airport as best as possible, can detect the movements of a person, be it a flight service user or an employee at the Lombok International airport. Aviation Security personnel must have the courage to take decisive action in dealing with unruly passangers or service users who do not comply with applicable regulations for the safety of service users at the airport and on the basis of operational standards that apply at Lombok International Airport.